Investigation of Engine Emission with Diesel-Palm Biodiesel-Antioxidant Blend - Choi, C.M.; Varman, M.; Masjuki, Haji Hassan (2017)
Similar properties ofbiodiesel to conventional diesel have made biodiesel as a promising fuel. However, its NOx emission was reported higher by most researchers in the world. In this study, antioxidants are used in the effort of improving the oxidation stability ofbiodiesel and reducing the NOx emission while maintaining the engine performance. p-Phenylenediamine (PPD) and N, N'-diphenyl-pphenylenediamine (DPPD) are added in 0.025 wt% and 0.15 wt% concentrations, respectively into palm oil methyl ester-diesel blend. The performance characteristics ofbiodiesel blends are tested on a single cylinder engine with an attached emission analyser. The addition of the PPD and DPPD antioxidants improved the oxidation stability of biodiesel without affecting much in the density and kinematic viscosity. For B20 (20% biodiesel + 80% Euro 5 diesel), the addition ofDPPD showed the best results by reducing NO (0.8% lower on average), CO (10.8% lower on average) and HC emission (32.9% lower on average), as compared to B7 blend. However, in terms of engine performance, B20+DPPD showed higher BSFC and lower brake power when compared to B7 blend.